Loss of Sirtuin 7 impairs cell motility and proliferation and enhances S-phase cell arrest after 5-fluorouracil treatment in head and neck cancer - Marta Halasa; Syeda Afshan; Anna Wawruszak; Agata Borkowska; Klaudia Brodaczewska; Alicja Przybyszewska-Podstawka; Joanna Kalafut; Marzena Baran; Adolfo Rivero-Müller; Andrzej Stepulak; Matthias Nees (Scientific Reports)
Abstract Sirtuin 7 (SIRT7), a member of the sirtuin family of NAD+-dependent deacetylases, plays a vital role in cancer, exhibiting context-dependent functions across various malignancies. Our study investigates the role of SIRT7 depletion in head and neck squamous cell carcinoma (HNSCC) progression. In vitro and 3D organotypic models demonstrated that SIRT7 knock-out attenuates cancer cell viability, proliferation, and motility as well as induces downregulation of migration- and epithelial-mesenchymal transition (EMT)-related gene expression. Moreover, the SIRT7 loss results in slower organoid formation and less invasive organoid morphology, validated by vimentin downregulation. The SIRT7 loss potentiates S-phase arrest in cell cycle progression after 5-FU treatment and elevates the ratio of dead cells. Additionally, SIRT7 deletion reduces the expression of G1 phase-associated proteins, Cyclin D and CDK4. Altogether, our study highlights SIRT7 as a promising therapeutic target in HNSCC, enhancing the effectiveness of treatment modalities such as combinational treatment.